Pengaruh Media Tanam dan Takaran Pupuk Cair terhadap Pertumbuhan Kelapa Sawit di Pembibitan Utama - Nopit Yohanes; Yakup Yakup (xxxx-xxxx, 2023)
Yohanes N, Yakup Y.  2022. Effect of planting media and liquid fertilizer dosage on oil palm growth in main nursery. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 641-650.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the advancements in oil palm cultivation is seeding techniques and the development of superior seeds. This study aimed to investigate the effect of manure on growing media and bio fertilizer is best to growth of oil palm seedlings in the main nursery. This research was conducted in the village of Suka Sari, District Alang-alang Lebar, Palembang. This research used Randomized Factorial Design (RAKF) with 3 replications. The first factor is manure treatment that consisted of three treatments P1 (0%), P2 (25%), P3 (50%), and the second factor giving biofitalik with three treatments and three times the B1 (5 cc/l), B2 (10 cc/l), B3 (15 cc/l). Observations were obtained concentrations of manure significant effect of the number of leaves, and no significant effect on plant height increment, increased girth, plant weight, root fresh weight and dry weight of roots. In general liquid fertilizer has not significantly influenced all parameters were observed. Interaction between treatment of manure and liquid fertilizer biofitalik no real effect.